INFLUENCE OF DISTRIBUTION TYPES OF CREDIT TO THE PROFITABILITY (STUDY AT PT. BANK BUKOPIN TBK. PERIOD 2009 – 2014) - Rina Maria Hendriyani (Value : Journal of Management and Business, 2017)
Bukopin Bank is one of the banking institutions that have vision is to become a leading financial institution in integrated financial services, its mission is to provide superior and comprehensive financial service solutions that meet customer need such personal, group or corporate business, to develop competitive Small and Medium Enterprise (SME), to build employees involvement to improve productivity for the employees welfare, to increase value-added investment for shareholders through prudent business management.The purpose of this research are: 1) to examine loans distribution which consist of consumer, micro, SME and commercial loans, 2) to assess profitability of Bukopin Bank, And 3) to analyze partial and simultaneous effect of loans distribution on profitability of Bukopin Bank.The research design is descriptive and verification research, which organize research variables into indicators that can be measured quantitatively so that it can be used as model of hypothesis testing. The research problem is causative research with multiple linear regression analysis.The effect of loans distribution on profitability of Bukopin Bank, period 2009 - 2014 can be concluded as follows: 1) loans distribution which consist of consumer, micro, SME and commercial loans has totally increased per year, 2) Profitability of Bukopin Bank is fluctuated in the period 2009 - 2014 and tend to decreased. In 2010 has increased 10.95%; 2011 increased 15.43%, but 2012 has decreased 2.14%, 2013 has decreased 4.37%; and the largest decrease was occurred in 2014 with the amount of 24.0%, and 3) results of hypothesis testing is known that there is a significant influence between loans distribution toward profitability of Bukopin Bank, either simultaneously or partially. The amount effect of loans distribution toward profitability that is 99.5%, and the rest is influenced by other factors except loans distribution.